Study on the impact of institutions on the labor productivity of private enterprises in Vietnam through the spillover effect from state-owned enterprises - Hong-Nham Nguyen Thi; Hong-Thuy Le Thi; The-Dong Phung (Economies, 2021)
The paper analyzes the impact of institutions on the labor productivity of small and medium-sized private enterprises through the spillover effect from state-owned enterprises (SOEs). The authors used data samples from three datasets: (i) The Annual Enterprise Survey conducted by the General Statistics Office of Vietnam (GSO) from 2010 to 2018; (ii) Institutional data (PCI) published by the Vietnam Chamber of Commerce and Industry (VCCI) from 2010 to 2018; (iii) GSO 2012 I-O balance sheet and a set of tabular data containing 666,221 observations at the enterprise and provincial levels in Vietnam from 2010 to 2018, including both listed and unlisted enterprises. The model's experimental result shows that institutional improvement boosts labor productivity of domestic private enterprises through a horizontal and forward spillover channel from SOEs. Through the backward spillover channel from SOEs, how institutional improvement affects the labor productivity depends on the degree of backward spillover channel from SOEs.
Keywords: 330; institution; labor productivity; private enterprise; spillover effect; state-owned enterprises (SOEs)